Tetanorhynchus leonardosi (Mello-Leitão) (Orthoptera: Proscopiidae), nova praga em eucaliptos - Flechtmann, Carlos A.H. [UNESP]; Ottati, Angelo L.T. [UNESP] (Sociedade Entomológica do Brasil, 1997)
We report for the first time the attack of the walking stick Tetanorhynchus leonardosi (Mello-Leitão) (Orthoptera: Proscopiidae) on young eucalyptus, Eucalyptus urophylla, in Brazil. The upper third of the trees was attacked (apical meristems and new leaves). During the hottest hours of the day the insects were found sheltered between leaves on the median third of the plants, and feeding when temperatures were milder. The attack was heterogeneous in the stand, being more concentrated when it was neighbouring an area of native 'Cerrado' vegetation. Mean defoliation was 5.8%, with an average of 5.2% of plants with apical meristems cut by the walking sticks. An application of Methyl Parathion was not effective against the pest. Apparently plants older than 6 months were less attacked by the insects, that preferred 3-month old trees. The reduction of native vegetation may explain the dispersion of T. leonardosi from its native host plants to the exotic eucalyptus.
Tetanorhynchus leonardosi (Mello-Leitão) (Orthoptera: Proscopiidae), a new eucalyptus pest
Keywords: Insecta; damage; dispersion; walking stick